Analisis Yuridis Perlindungan Hukum bagi Nasabah atas Kerugian Kehilangan Saldo pada Aplikasi BRIMO Berdasarkan Undang-Undang Nomor 10 Tahun 1998 tentang Perbankan - Alequesty Mariani Pandu; Orpa Juliana Nubatonis; Rini Marselin Kaesmetan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid development of digital banking has improved the efficiency and accessibility of financial services while simultaneously increasing the risk of cybercrime, particularly phishing, unauthorized access, and the loss of customers’ funds. This study aims to analyze the legal protection available to customers who suffer financial losses due to balance depletion in the BRIMO application and to examine the legal liability of banks under Law Number 10 of 1998 concerning Banking. This research employed normative legal research using statutory and conceptual approaches. The legal materials consisted of primary, secondary, and tertiary legal sources analyzed through qualitative descriptive methods. The findings indicate that legal protection for banking customers is provided through preventive measures, including the application of the prudential principle, information technology risk management, personal data protection, and customer education, as well as repressive measures through dispute resolution mechanisms. However, the existing legal framework has not specifically regulated the allocation of liability in digital banking transactions. Banks may be held liable when losses result from weaknesses in security systems or failures in implementing risk management. Therefore, more specific regulations are required to strengthen legal certainty and ensure balanced legal protection for both banks and customers in the digital banking sector.